Removal of methylene blue by seed-watermelon pulp-based low-cost adsorbent: Study of adsorption isotherms and kinetic models. Issue 8 (3rd August 2017) - Chen, Cheng; Fu, Ye; Yu, Li-li; Li, Jun; Li, De-qiang
ABSTRACT: Based on the abundance of seed-watermelon pulp (SWP) in Xinjiang, China, SWP was employed to prepare low-cost adsorbent toward the removal of methylene blue (MB). The effects of contact time at different initial concentration were studied. The widely used adsorption isotherm models including Langmuir, Freundlich, and Temkin isotherms were employed to depict the adsorption process. The Langmuir isotherm was best fitted to the experimental data. Batch kinetic studies showed that an equilibrium time of 300 minutes was needed for the adsorption. The adsorption properties can be well described by pseudo-second-order kinetic model and the MB uptake was not controlled by intraparticle diffusion mechanism. GRAPHICAL ABSTRACT: